The Transient FSI Simulation for Aeroelastic Evaluation of a Low Subsonic Wing in Cruise Flight Regime - Jayadi, Muhamad (Jurnal Teknologi Kedirgantaraan, 2025)
This study presents a fluid-structure interaction (FSI) analysis of a low subsonic aircraft wing under cruise conditions. Using computational fluid dynamics (CFD) coupled with structural finite element analysis, the lift and drag coefficients, wing deformation, and structural stresses were simulated over a 5-second interval with a 0.1-second timestep. The simulations revealed that the lift and drag coefficients converged to 0.136 and 0.0456, respectively. Maximum wing deformation was recorded at 4.78 mm, and the highest stress was 2.765 MPa. A calculated safety factor of 309.78 confirms that the wing structure remains well within safe limits under the specified aerodynamic loading. These findings validate the structural integrity of the wing during steady cruise and underscore the effectiveness of FSI simulation in evaluating aeroelastic performance forces